Maternal and Placental Factors Associated with Congenital Hearing Loss in Very Preterm Neonates - Shin Hye Kim; Byung Yoon Choi; Jaehong Park; Eun Young Jung; Soo-Hyun Cho; Kyo Hoon Park (Pediatrics and Neonatology)
Sensorineural hearing loss (SNHL) is a multifactorial disease that more frequently affects preterm newborns. Although a number of maternal conditions have been reported to be associated with preterm birth, little information is available concerning maternal risk factors for the development of SNHL. We aimed to identify maternal and placental risk factors associated with a “refer” result on the newborn hearing screening (NHS) test and subsequently confirmed SNHL in very preterm neonates. Methods: This retrospective cohort study included 267 singleton neonates who were born alive after ≤ 32 weeks. Histopathologic examination of the placenta was performed, and clinical data were retrieved from a computerized perinatal database. Cases with two abnormal findings, “refer” on the NHS test, and presence of SNHL on the confirmation test were retrospectively reviewed based on electronic medical records. Results: Forty-two neonates (15.7%) showed a “refer” result, and, on the confirmation test, permanent SNHL was identified in 1.87% (5/267) of all neonates. Multivariate regression analysis revealed that the presence of funisitis was independently associated with a “refer” on the NHS test, whereas use of antenatal corticosteroids was statistically significantly associated with a reduced incidence of “refer” on the screening test. Neither histologic chorioamnionitis nor prematurity (as defined by low gestational age and birth weight) was associated with a “refer” on the NHS test. By contrast, multivariate analysis with occurrence of SNHL as a dependent variable identified no significant associations with the parameters studied, probably owing to the small total number of neonates with permanent SNHL. Conclusion: Presence of funisitis was significantly and independently associated with increased risk of abnormal NHS results, while administration of antenatal corticosteroids was related to a normal NHS result. These findings support the hypothesis that a systemic fetal inflammatory response, manifested as funisitis, might play a role in the pathogenesis of SNHL in preterm neonates.